Methodological approach for the use of agricultural transformation losses based on lean manufacturing: Case Study on a coffee farm in Colombia - Hualpa-Zúñiga, Andres (2024)
Improvements in production systems that use the lean manufacturing approach known as “Lean” have the objective of eliminating or reducing waste or process inefficiencies (muda). This approach is increasingly adopted by different industrial sectors, including agriculture. Although Lean improvements are traditionally applied to existing processes from cultivation to distribution, opportunities to intervene in processing wastes (losses) are left aside. This article presents a methodological approach framed in five Lean principles, made up of six activities aimed at the design of new processes that make use of the losses generated by harvesting and agricultural transformation. The methodological approach is applied in a Colombian coffee farm where parchment coffee transformation processes are developed. A parallel losses composting process is designed that transforms defective, green, overripe beans, coffee pulp, mucilage and husk. The results show that by applying the methodological approach on the coffee farm, a level of losses transformation of 86% is achieved. Molting is also reduced for both the current parchment coffee production line and the composting line to 35% and 50% respectively. The main reductions are reprocessing and waiting times. Finally, a 30.3% reduction is obtained in the time of activities that do not add value, making both the current and proposed processes more efficient and with better delivery times.